2019
DOI: 10.1186/s40621-019-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a novel sign’s impact on whether park visitors enter a dangerous river

Abstract: BackgroundBetween 1972 and 2015, 56 visitors to the two national parks that border the Potomac River Gorge experienced fatal drowning. In 2016, the George Washington Memorial Parkway (GWMP), and the Chesapeake and Ohio National Historical Park (CHOH) partnered with a researcher to see if enhancement of their risk communication strategies could reduce behaviors that contribute to these deaths.MethodsAn experimental sign, which informed visitors that water entry was illegal and could result in a fine exceeding $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Several previous studies have examined warning sign attention and compliance, testing the effectiveness of different messages, although mostly in the context of natural resource protection (Ballantyne & Hughes, 2006;Bradford & McIntyre, 2007;Cialdini et al, 2006;Girasek, 2019;Hall et al, 2010;Hockett & Hall, 2007;Johnson & Swearingen, 1992;Marschall et al, 2017;Park et al, 2008;Reiner & Lawson, 2009;Schwartz, et al, 2018;Winter, 2006). A variety of theoretical perspectives are represented in these studies.…”
Section: Normative Warning Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have examined warning sign attention and compliance, testing the effectiveness of different messages, although mostly in the context of natural resource protection (Ballantyne & Hughes, 2006;Bradford & McIntyre, 2007;Cialdini et al, 2006;Girasek, 2019;Hall et al, 2010;Hockett & Hall, 2007;Johnson & Swearingen, 1992;Marschall et al, 2017;Park et al, 2008;Reiner & Lawson, 2009;Schwartz, et al, 2018;Winter, 2006). A variety of theoretical perspectives are represented in these studies.…”
Section: Normative Warning Messagesmentioning
confidence: 99%
“…A final limitation of our study was that we only studied the effectiveness of different normative messages; therefore, we don't know if normative messages are more or less effective than other types of information, such as possible sanctions for rule breaking. For example, some studies have found that adding sanctions to messages about park regulations increased compliance (Girasek, 2019;Gramman et al, 1995;Johnson & Swearingen, 1992). However, focusing on normative messages is appropriate for this study because normative messages seem to be commonly used.…”
Section: Limitationsmentioning
confidence: 99%
“…Twenty-two studies were included in the review (Table 2). The majority (n = 16) [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] were from HICs; six [54][55][56][57][58][59] were from LMICs. Australia (n = 7) [38,39,43,46,48,52,53] and the US (n = 6) [40-42, 47, 49, 51] were the two most represented geographical locations, representing over half of included studies.…”
Section: Setting Duration and Evaluation Designmentioning
confidence: 99%
“…Studies using observational data noted the potential for observational bias or misclassification of data [39,40,42,61]. Girasek (2019) stated that the introduction of a camera may have influenced behaviour and enhanced the effectiveness of the intervention.…”
Section: Self-reported Study Limitationsmentioning
confidence: 99%
“…Given deviation of existing signage from best practice principles and that signs and education in general have had variable [ 27 , 32 ] but occasionally substantial positive effect on behavior of the target audience [ 27 , 30 ], we think more effective signage might be able to make a meaningful contribution to conservation of spinner dolphins in the Hawaiian Islands. More specifically, we believe such signs could reduce proscribed behavior [ 30 , 31 , 33 , 34 ], be more cost effective than enforcement of regulations [ 35 , 36 ], and dramatically reduce litigation costs by making it clear that those who violated the law had ample opportunity to learn about it.…”
Section: Introductionmentioning
confidence: 99%